Sport specific adaptation in rotation range of motion in the elite Golfer' s shoulder - Mackenzie, T. A.; Herrington, L.; Funk, L.; Horlsey, I.; Cools, A. (Journal of Athletic Enhancement, 2016)
Objective: Shoulder rotation in golfers is thought to determine the length of the back swing, which in turn influences club-head speed and ball drive distance. In athletes a decrease in shoulder internal rotation in the dominant shoulder when compared with the opposite side has been noted and is associated with increased risk of shoulder injury. It was hypothesised that golfers would bilaterally have more rotation range of motion compared to controls and that golfers would exhibit a unique pattern of rotation range of motion between their dominant and non-dominant/lead shoulders. The aim of the study was to compare rotation range of shoulder motion within and between male elite golfers and male non-athlete controls. Method: Forty five male golfers on European Challenge Tour and thirty six non-athlete control volunteers meet the inclusion criteria for the study. An inclinometer was used to determine the passive shoulder rotation range with the participant in supine. Results: Golfers` shoulders have significantly more rotation range than controls in total arc of rotation (dominant side Delta15.30°, nondominant/lead side Delta21.98°, p=0.01) and in external rotation (dominant side Delta7.94°, non-dominant/lead side Delta11.04°, p=0.01). In golfers there are no differences in side to side comparison in: shoulder total arc of rotation (p=0.48), internal rotation (p=0.52), or in external rotation (p=0.54). Conclusion: Golfers` shoulders have significantly more range than controls in total arc of rotation and in external rotation but the professional golfers in this study were not found to have a unique pattern of shoulder rotations between sides. This study endorses screening of shoulder rotation range in healthy elite professional golfers using side to side comparison. If unique loss of range is noted between sides in the context of a loss of total rotation range it may have consequences for the efficacy of the swing technique and potentially imply risk to injury